Severe Disseminated Infection with Emerging Lineage of Methicillin-Sensitive Staphylococcus aureus - Paul Jewell; Luke Dixon; Aran Singanayagam; Rohma Ghani; Ernie Wong; Meg Coleman; Bruno Pichon; Angela Kearns; Georgina Russell; James Hatcher (Emerging Infectious Diseases, 2019)
We report a case of severe disseminated infection in an immunocompetent man caused by an emerging lineage of methicillin-sensitive Staphylococcus aureus clonal complex 398. Genes encoding classic virulence factors were absent. The patient made a slow recovery after multiple surgical interventions and a protracted course of intravenous flucloxacillin.